Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Operasional Pada PT. Bandar Krida Jala (BKJL) Patimban Subang - Andrian, Andrian; Vrans Romi, Mochamad (Jurnal Ragam Pengabdian, 2026)
This study aims to determine the partial and simultaneous effects of work discipline and work motivation on the performance of operational employees at PT. Bandar Krida Jala (BKJL) Patimban, Subang. The study employs a quantitative method with descriptive and associative approaches. Data were collected through questionnaires, interviews, and documentation involving 60 operational employees and subsequently analyzed using multiple linear regression with the aid of SPSS version 27. The results indicate that work discipline falls into the "moderate" category, work motivation into the "high" category, and employee performance into the "good" category. Hypothesis testing reveals that work discipline has a positive and significant effect on employee performance (tcount = 3.978), as does work motivation (tcount = 8.138). Simultaneously, work discipline and work motivation significantly influence employee performance (Fcount = 103.587), with a coefficient of determination of 78.4%, while the remaining 21.6% is influenced by factors outside the scope of this study. Based on these findings, it is recommended that the company enhance discipline and provide employee rewards to maintain and improve operational performance.